IMPLEMENTASI ADMINISTRASI SEKOLAH DASAR NEGERI - Yustina Tri Lestari (Manajer Pendididikan, 2015)
The purpose of this study to describe the administration of the primary school 164 Seluma.The method in this research using descriptive qualitative method. The conclusions of thestudy implementation are: first, the administration of student work effectively. All students complete administrative requirements and well-crafted. Second, in the administration ofeducational staff includes academic qualifications and competence of teachers and education personnel. Third, the administrative activities of the school is able to operate effectively despite the power administras ie TU no. Fourth, the implementation of the financial administration refers to standard financing consisting of: investment costs, operating costs and, personal expenses. Fifth, in the administration there is a problem that affects not effective implementation of theadministration.Keywords: implementastion, elementary school, administration